Oral Health-Related Quality of Life among children ages 14-16 in Diliman Preparatory School for AY 2016-2017 - Cadavez, Michelle June B.
INTRODUCTION: It is important to determine the correlation of oral health status of adolescents and their oral health-related quality of life (OHRQoL) because it is during this stage of their life when they are more susceptible to dental caries experience (Moynihan & Petersen, 2004). One method of measuring OHRQoL is the Child Oral Health Impact Profile Short Form or COHIP-SF19 (Broder et al, 2012). This study aims to determine the correlation between oral health status and quality of life among 14-16 years old in Diliman Preparatory School.